2022
DOI: 10.1101/2022.01.16.476546
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conserved Untranslated Regions of Multipartite Viruses: Natural Markers of Novel Viral Genomic Components and Tags of Viral Evolution

Abstract: Viruses with split genomes are categorized as being either segmented or multipartite according to whether their genomic segments occur in single or different virions. Some complexity will exist, in that inherited “core” vital segments viruses may renew the others once host and environmental alterations keep driving viral evolution. Despite this uncertainty, empirical observations have been made across the split genomes in the untranslated regions (UTRs) on the short or long stretches of conserved or identical … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…When the 3′-termini of the cileviruses CiLV-C, CiLV-C2, and PfGSV were included in the alignment, the presence of highly conserved nucleotide sequences in all these viruses became evident, likely denoting the putative functional role of these sequences as described in other viruses ( Dreher, 1999 ; Liu et al, 2020 ; Rasekhian et al, 2021 ). The implementation of the UTR-backed iterative BLASTN approach ( Zhang et al, 2022 ) using the 3′-terminus conserved nucleotide sequences of SvRSV, LigCSV, and LigLV, resulted in the recovery of contigs corresponding to the RNA1 and RNA2 segments already known, and new putative genomic segments were not identified.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the 3′-termini of the cileviruses CiLV-C, CiLV-C2, and PfGSV were included in the alignment, the presence of highly conserved nucleotide sequences in all these viruses became evident, likely denoting the putative functional role of these sequences as described in other viruses ( Dreher, 1999 ; Liu et al, 2020 ; Rasekhian et al, 2021 ). The implementation of the UTR-backed iterative BLASTN approach ( Zhang et al, 2022 ) using the 3′-terminus conserved nucleotide sequences of SvRSV, LigCSV, and LigLV, resulted in the recovery of contigs corresponding to the RNA1 and RNA2 segments already known, and new putative genomic segments were not identified.…”
Section: Resultsmentioning
confidence: 99%
“…Viral segments of SvRSV, LigCSV, LigLV, and those of typical cileviruses were aligned using MAFTT ( Katoh and Standley, 2013 ) and visualized using the Jalview program ( Procter et al, 2021 ). Sequences comprising 90–120 nts of the highly conserved 3′ untranslated regions (UTR) of SvRSV, LigCSV, and LigLV were used to search for the presence of putative non-detected viral segments in the HTS-contigs libraries using the UTR-backed iterative BLASTN approach ( Zhang et al, 2022 ). Previously, BLASTN databases were built from the HTS-contig libraries of each sample using Geneious software package v 11.1.4 ( Kearse et al, 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…The four grapevine samples analyzed in this fashion showed evidence of GaJV-1 infection, with two of them, i31 and i33, showing the most reads for GaJV-1 genomic RNAs (respectively, 1.6 and 1.5% of total reads). Further analysis was therefore focused on the contigs assembled for the i31 sample, allowing the identification, as reported independently [ 17 , 18 ], of homologies in the 5′ and 3′ non-coding regions (NCRs) of the contigs for the three GaJV-1 genomic RNAs. These conserved 5′ and 3′ NCRs were then used in BLASTN searches of all the contigs assembled from these two samples.…”
Section: Resultsmentioning
confidence: 99%
“…The notion that the genomes of jiviviruses may contain additional genome segments of the three previously identified was recently proposed on the basis of a datamining study investigating conserved genome ends [ 18 ]. However, this study only identified one additional segment for GaJV-1 and two additional segments in two viruses identified from pecan datasets and that are presumably identical to the CaJV-1 and CaJV-2 viruses reported here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation